Personality, depressive symptoms and prior trauma exposure of new recruits at two Metropolitan Police Service academies in South Africa - U Subramaney; E Libhaber; N Pitts; M Vorster (South African Journal of Psychiatry, 2012)
Background. Police officers are predisposed to trauma exposure. The development of depression and post-traumatic stress disorder (PTSD) may be influenced by personality style, prior exposure to traumatic events and prior depression.